Penerapan Metode Smarter Dalam Pemilihan Guru Terbaik - Muhamad Rosdiana; Erdi Sutriyatna (CV. Multi Kreasi Media, 2024)
The selection of the best teachers is carried out to give appreciation to teachers in increasing teacher motivation and quality. The selection of the best teachers at SMK Negeri 8 Tangerang Regency is still carried out conventionally, namely by determining based on the results of discussions by the Principal and his staff. We provide a solution for selecting the best teachers using the SMARTER method or Simple Multi Attribute Rating Technique Ranks. With this method, 6 relevant criteria are given by weighting each criterion so that it will produce a more objective value. Weights are calculated using the Range Order Centroid (ROC) formula. This ROC is based on the priority level of the criteria. From these scores, a ranking is then carried out which will produce the best score and will become a reference for determining the best teacher.